1999
DOI: 10.1089/088922299310935
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of a Live Recombinant Canarypox Virus Expressing HIV Type 1 gp120 MN tm/gag/protease LAI (ALVAC-HIV, vCP205) Followed by a p24E-V3 MN Synthetic Peptide (CLTB-36) Administered in Healthy Volunteers at Low Risk for HIV Infection

Abstract: A live recombinant canarypox vector expressing HIV-1 gpl20 MN tm/gag/protease LAI (ALVAC-HIV, vCP205) alone or boosted by a p24E-V3 MN synthetic peptide (CLTB-36) was tested in healthy volunteers at low risk for HIV infection for their safety and immunogenicity. Both antigens were well tolerated. ALVAC-HIV (vCP205) induced low levels of neutralizing antibodies against HIV-1 MN in 33% of the volunteers. None of them had detectable neutralizing antibodies against a nonsyncytium-inducing HIV-1 clade B primary iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…While DCs may play a role in the pathogenesis of these infections, they are also likely to be critical in activating virus-specific immune responses. Recombinant avipox virus constructs have proven to be both immunogenic and safe in humans (6,15,19,32,34,49) and are, therefore, of great interest in vaccine research. One study was published on the use of recombinant fowlpox virus for the transfer of genes to DCs (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While DCs may play a role in the pathogenesis of these infections, they are also likely to be critical in activating virus-specific immune responses. Recombinant avipox virus constructs have proven to be both immunogenic and safe in humans (6,15,19,32,34,49) and are, therefore, of great interest in vaccine research. One study was published on the use of recombinant fowlpox virus for the transfer of genes to DCs (8).…”
Section: Discussionmentioning
confidence: 99%
“…ALVAC constructs encoding foreign proteins have been shown to induce humoral and cellular immune responses against a variety of infectious pathogens. These include rabies virus (19,58), feline immunodeficiency virus (59), human immunodeficiency virus type (HIV-1) and HIV-2 (1,4,6,15,18,35,49), Japanese encephalitis virus (32,43), rabbit hemorrhagic disease virus (17), and canine distemper virus (CDV) (39,55), as well as tumor antigens (25,34,46). In fact, very recent studies revealed that mucosal application of ALVAC containing CDV genes induced high titers of neutralizing antibodies (Abs) and protection against a mucosal challenge with CDV (63).…”
mentioning
confidence: 99%
“…As all patients in the cohort were more than 30 years old, they were likely to have been vaccinated against smallpox, and it is known that responses to vaccinia virus are long lived even in HIV-infected individuals (13). In prior canarypox vaccine studies, control vectors were not used at the stimulation level to monitor responses in vitro (5,11,17,19,21,22,48). Our study emphasizes that it is critical to use control vectors to establish the specificity of HIV-specific responses.…”
Section: Vol 75 2001 Canarypox Virus-infected Dcs Induce Anti-hiv Tmentioning
confidence: 99%
“…Recombinant canarypox viruses administered intramuscularly have an excellent safety profile in humans, but their immunogenicity has been disappointing. Seronegative individuals who have been vaccinated with ALVAC constructs expressing HIV-1 genes demonstrate intermittent responses of variable magnitude (48). This may be because the vectors fail to be acquired by potent APCs such as DCs.…”
Section: Vol 75 2001 Canarypox Virus-infected Dcs Induce Anti-hiv Tmentioning
confidence: 99%
“…Canarypox vectors containing HIV-1 gene inserts have undergone extensive testing in phase I-II trials. Notably, live recombinant canarypox ALVAC-HIV vaccine (vCP205), 3 containing HIV-1 genes encoding env, gag, and portions of pol, has induced cumulatively HIV-specific CD8 ϩ CTL in the peripheral blood of 30 -50% of HIV-seronegative vaccine recipients (22)(23)(24). However, vaccine-induced mucosal CTL responses have not been assessed in these studies, and heretofore it has been unclear whether examination of sufficient numbers of mucosal T cells was feasible without subjecting volunteers to more invasive procedures to obtain the relevant mucosal samples.…”
mentioning
confidence: 99%